(untitled) (Symposium on Natural and Applied Sciences, 2026)
Intrauterine blood transfusion (IUHT) is a highly effective treatment for severe fetal anemia, significantly reducing perinatal mortality rates and improving pregnancy outcomes. The most common reason for IUHT remains hemolytic disease of the fetus due to Rh alloimmunization. However, in recent years, the indications for this procedure have expanded to include anemia due to parvovirus infection, fetomaternal hemorrhage, twin-to-twin transfusion syndrome, and certain hereditary blood disorders. Modern advances in ultrasound diagnostics, middle cerebral artery Doppler ultrasound, improved invasive techniques, and advances in fetal medicine have significantly improved the safety and effectiveness of the procedure.